PRODUKSI IMMUNOMODULATOR DARI PROBIOTIK ALAMI UNTUK KESEHATAN MASYARAKAT - Andalia, Winny; Pratiwi, Irnanda; Ramayanti, Cindi (Jurnal Abdimas Musi Charitas, 2023)
The immune system is an important factor in human health. High immunity will prevent attacks from various diseases. However, with various activities, poor eating patterns, unhealthy lifestyles, and the environment, the immune system in humans will decrease. This motivates researchers in the field of health and humanity to produce immunomodulators. In this community service activity, immunomodulators are produced by utilizing bovine colostrum to produce Socio Imun immunomodulator drinks. For 1 production using 1 kg of cow colostrum and other additives, 100 bottles of 250 ml of immunomodulator will be produced. From the results of this activity, people can consume immunomodulators as an immune booster. By increasing the body's immune system, the risk of disease symptoms in the community can be reduced.